Altered post-stroke propulsion is related to paretic swing phase kinematics - Dean, Jesse C. (Clin Biomech (Bristol, Avon), 2019)
BACKGROUND: Gait propulsion is often altered following a stroke, with clear effects on anterior progression. Changes in the pattern of propulsion could potentially also influence swing phase mechanics. The purpose of the present study was to investigate whether post-stroke variability in paretic propulsion magnitude or timing influence paretic swing phase kinematics. METHODS: 29 chronic stroke survivors participated in this study, walking on an instrumented treadmill at their self-selected and fastest-comfortable speeds. For each participant, we calculated several propulsion-related metrics derived from anteroposterior ground reaction force or from center of mass power, as well as knee flexion angle and circumduction displacement during the swing phase. We performed a series of linear mixed model analyses to determine whether the propulsion metrics for the paretic leg were related to paretic swing phase mechanics. FINDINGS: A subset of the stroke survivors exhibited unusual braking forces late in the paretic stance phase, when strong propulsion typically occurs among uninjured controls. Beyond the effects of walking speed or walking condition, these braking forces were significantly linked with altered paretic swing phase mechanics. Specifically, large braking impulses were associated with reduced paretic knee flexion (p=0.039) and increased paretic circumduction (p=0.023). INTERPRETATION: The present results suggest that braking forces late in stance are particularly indicative of deficits in the production of typical swing phase kinematics. This relationship suggests that therapies designed to address altered swing kinematics should also consider altered force generation in late stance, as these behaviors appear to be coupled.